Integration taxes and gestural integration: Access and limits to integration through new citizens’ participation in state-sponsored grassroots volunteerism in Singapore - WONG, George (Institutional Knowledge at Singapore Management University, 2023)
Integration is a contested topic in Singapore’s public discourse. One such area is integration through state-sponsored grassroots community volunteerism. Little is however known about such experiences of grassroots volunteerism to integration outcomes. This paper addresses the gap by exploring how new citizen and permanent resident grassroots volunteers make sense of their experiences through ‘integration taxes' and ‘gestural integration'. In doing so, this paper argues that while grassroots volunteerism offers lower barriers to entry for new citizens, it constraints the diversity of integration by and through new citizen volunteers due to discrimination, marginalisation and staged integration faced in grassroots work.